VD_FINDINFO HC / 2016 / 14 vom 4. Januar 2016 - VD Tribunal cantonal (2016)
RETARD INJUSTIFIÉ, EXPERTISE, LIQUIDATION DU RÉGIME MATRIMONIAL, SUSPENSION DE LA PROCÉDURE | 126 al. 1 CPC (CH), 126 al. 2 CPC (CH), 319 let. b ch. 2 CPC (CH), 319 let. c CPC (CH)